2021
DOI: 10.1155/2021/8828326
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Characteristics and Pathological Types of Hyperproliferation of Gastric Surface Epithelial Cells

Abstract: Objective. To investigate the histomorphological characteristics and pathological types of hyperproliferation of gastric surface epithelial cells. Methods. Hematoxylin and Eosin, Periodic acid–Schiff, and immunohistochemical staining were performed on biopsy specimens obtained from 723 patients with hyperproliferation of gastric surface epithelial cells and/or hyperplasia of gastric pits. Follow-up gastroscopic reexaminations were performed on 475 patients included. Improvement probability was analyzed using K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As such, the method cannot reflect the histopathological characteristics, nor can it provide any information about the relationship between clinical Hp infection and gastric cancer, and is not conducive to evaluating the relationship between Hp infection and carcinogenesis. The authors' previous study found that Hp infection caused a papilloma-like proliferation of glandular epithelial cells 11 and also led to extensive segmental atrophy of the glands in the lamina propria of the gastric mucosa. 12 The World Health Organization classified Hp infection as a carcinogen of gastric cancer, accordingly, giving rise to a trend to eliminate Hp to prevent gastric cancer through the detection and treatment of the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the method cannot reflect the histopathological characteristics, nor can it provide any information about the relationship between clinical Hp infection and gastric cancer, and is not conducive to evaluating the relationship between Hp infection and carcinogenesis. The authors' previous study found that Hp infection caused a papilloma-like proliferation of glandular epithelial cells 11 and also led to extensive segmental atrophy of the glands in the lamina propria of the gastric mucosa. 12 The World Health Organization classified Hp infection as a carcinogen of gastric cancer, accordingly, giving rise to a trend to eliminate Hp to prevent gastric cancer through the detection and treatment of the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…There is some literature available on how to differentiate the severity and stage of MALT lymphoma using histopathological morphology, and this is beneficial for clinicians to provide accurate treatment. In our previous study, we found that H. pylori infection resulted in vacuolar degeneration and papillary proliferation of the glandular epithelium of the gastric mucosa [9] and the gastric mucosa infected by H. pylori showed excessive upward migration and insufficient downward proliferation in the affected regions, resulting in disordered proliferation of stem cells [10].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Helicobacter pylori infection can lead to a papillary proliferation of the surface epithelial cells. 10 However, how Hp infection leads to gastric mucosa atrophy and the histological structural, as well as the cellular morphological changes that occur during its onset and development, have not been reported. This study aimed to investigate the occurrence and development of Hp infection and its histomorphological features, providing a reliable pathological basis for precise treatment by clinicians.…”
Section: Introductionmentioning
confidence: 99%